AB0177 RHEUMATOID ARTHRITIS SAUDI DATABASE (RASD): A SINGLE CENTER EXPERIENCE. (2nd June 2020) - Hassan, R.; Cheikh, M.; Almoallim, H.; Faruqui, H.; Alquraa, R.; Eissa, A.; Alhazmi, A.; Janoudi, N.
Abstract : Background: National Registries are essential to direct current practice and design appropriate management strategies 1 . Rheumatoid arthritis (RA) registries in the middle east and north Africa remain scarcely represented 2 . Objectives: Our objective is to describe the Saudi RA population and to compare the findings to internationally reported data. Methods: This is a cross sectional, analytical study that was conducted at Doctor Soliman Fakeeh Hospital (DSFH). The study ran from December of 2014 and concluded in December of 2018 using a pool of 433 patients. Inclusion criteria included adults older than 18 years of age who fulfilled the 2010 American College of Rheumatology criteria for diagnosis of RA 3 . Data were collected from patients and entered in a specially designed program for this registry. They included main demographic details, , lag times to final disease diagnosis. Disease Activity Score-28-C Reactive Protein (DAS-28-CRP) was calculated on presentation and on subsequent visits with intervals ranging from three to six months between them. Multiple regression model was used to assess the predictors of disease activity. We charted the lines of medications given, including conventional and biologic disease modifying antirheumatic drugs (DMARDs), following treat to target strategies 4 . Results: Out of 430 patients, 76.68% were female, while only 23.32% were male and the mean age was found to be 49.26 years with SD±11. At initial presentation, 45.5% had demonstrated active disease (moderate or high disease activity) based on DAS-28-CRP scores while 54.5% were in remission or low disease activity. Out of the total number of clinic visitors, 330 had regular follow ups for more than 1 year while 103 patients were either irregularly visiting the rheumatology clinic or had lost follow up. The remission rates after 1 year had increased to 79.7% (263 patients), while 9.7% (32 patients) had low disease activity and no patients had sustained high disease activity at the end of follow up. It was also found that the female gender, higher Health Assessment Questionnaire-Disability Index (HAQ-DI) and a longer lag1/lag2 period were associated with higher disease activity in our population. Biologic medications had been used by 129 patients (29.7%) while conventional DMARDs were given to 304 patients (70.3%). Conclusion: We described a population of RA patients in a single center in SA. We detected higher remission rates at one year of follow up. This could be attributed to many factors, including good referral systems and treat to target strategies with easier access to biologic medications. References: [1]Singh JA, Saag KG, Bridges SL Jr, Akl EA, Bannuru RR, Sullivan MC, Vaysbrot E, McNaughton C, Osani M, Shmerling RH, Curtis JR, Furst DE, Parks D, Kavanaugh A, O'Dell J, King C, Leong A, Matteson EL, Schousboe JT, Drevlow B, Ginsberg S, Grober J, St Clair EW, Tindall E, Miller AS, McAlindon T. 2015 American College of Rheumatology Guideline for the Treatment of Rheumatoid Arthritis. Arthritis Rheumatol. 2016 Jan;68(1):1-26. [2]Smolen, Josef S., et al. "EULAR recommendations for the management of rheumatoid arthritis with synthetic and biological disease-modifying antirheumatic drugs: 2013 update." Annals of the rheumatic diseases 73.3 (2014): 492-509. [3]Saag KG, Teng GG, Patkar NM, Anuntiyo J, Finney C, Curtis JR, et al. American College of Rheumatology 2008 recommendations for the use of nonbiologic and biologic disease-modifying antirheumatic drugs in rheumatoid arthritis. Arthritis Rheum 2008;59 : 762–84. [4]Hussain W, Noorwali A, Janoudi N. From symptoms to diagnosis: an observational study of the journey of rheumatoid arthritis patients in Saudi Arabia. Oman Med J. 2016;31(1):29. Disclosure of Interests: Rola Hassan Grant/research support from: Pfizer pharmaceuticals, Mohamed Cheikh Grant/research support from: Pfizer pharmaceuticals, Hani Almoallim Grant/research support from: Pfizer pharmaceuticals, Hanan Faruqui Grant/research support from: Pfizer pharmaceuticals, Reem AlQuraa Grant/research support from: Pfizer pharmaceuticals, Ayman Eissa Grant/research support from: Pfizer pharmaceuticals, Aous Alhazmi Grant/research support from: Pfizer pharmaceuticals, Nahid Janoudi Grant/research support from: Pfizer pharmaceuticals